Virologic response to first-line efavirenz- or nevirapine-based antiretroviral therapy in HIV-infected African children - Kekitiinwa, A; Szubert, A; Spyer, M; Katuramu, R; Musiime, V; Mhute, T; Bakeera-Kitaka, S; Senfuma, O; Walker, A; Gibb, D; ARROW Trial Team (Lippincott, Williams & Wilkins, 2017)
BACKGROUND: Poorer virologic response to nevirapine- versus efavirenz-based antiretroviral therapy (ART) has been reported in adult systematic reviews and pediatric studies. METHODS: We compared drug discontinuation and viral load (VL) response in ART-naïve Ugandan/Zimbabwean children ≥3 years of age initiating ART with clinician-chosen nevirapine versus efavirenz in the ARROW trial. Predictors of suppression <80, <400 and <1000 copies/mL at 36, 48 and 144 weeks were identified using multivariable logistic regression with backwards elimination (P = 0.1). RESULTS: A total of 445 (53%) children received efavirenz and 391 (47%) nevirapine. Children receiving efavirenz were older (median age, 8.6 vs. 7.5 years nevirapine, P < 0.001) and had higher CD4% (12% vs. 10%, P = 0.05), but similar pre-ART VL (P = 0.17). The initial non-nucleoside-reverse-transcriptase-inhibitor (NNRTI) was permanently discontinued for adverse events in 7 of 445 (2%) children initiating efavirenz versus 9 of 391 (2%) initiating nevirapine (P = 0.46); at switch to second line in 17 versus 23, for tuberculosis in 0 versus 26, for pregnancy in 6 versus 0 and for other reasons in 15 versus 5. Early (36-48 weeks) virologic suppression <80 copies/mL was superior with efavirenz, particularly in children with higher pre-ART VL (P = 0.0004); longer-term suppression was superior with nevirapine in older children (P = 0.05). Early suppression was poorer in the youngest and oldest children, regardless of NNRTI (P = 0.02); longer-term suppression was poorer in those with higher pre-ART VL regardless of NNRTI (P = 0.05). Results were broadly similar for <400 and <1000 copies/mL. CONCLUSION: Short-term VL suppression favored efavirenz, but long-term relative performance was age dependent, with better suppression in older children with nevirapine, supporting World Health Organization recommendation that nevirapine remains an alternative NNRTI.